2021
DOI: 10.3390/cells10020237
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytic Connexin43 Channels Regulate Bone–Muscle Crosstalk

Abstract: Bone–muscle crosstalk plays an important role in skeletal biomechanical function, the progression of numerous pathological conditions, and the modulation of local and distant cellular environments. Previous work has revealed that the deletion of connexin (Cx) 43 in osteoblasts, and consequently, osteocytes, indirectly compromises skeletal muscle formation and function. However, the respective roles of Cx43-formed gap junction channels (GJs) and hemichannels (HCs) in the bone–muscle crosstalk are poorly underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Moreover, osteocytes abundantly express Cx43 proteins, which form both gap junctions and hemichannels. Cx43 gap junctions can facilitate the passage of small signaling molecules between coupled cells, whereas Cx43 hemichannels can mediate communication between the cell and the extracellular environment [ 34 ]. Herein, we found that HiSMF can promote the expression of Cx43 protein in osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, osteocytes abundantly express Cx43 proteins, which form both gap junctions and hemichannels. Cx43 gap junctions can facilitate the passage of small signaling molecules between coupled cells, whereas Cx43 hemichannels can mediate communication between the cell and the extracellular environment [ 34 ]. Herein, we found that HiSMF can promote the expression of Cx43 protein in osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Osteocytes, the most abundant cells in bone tissue, are descended from mature, matrix-producing osteoblasts and play a key role in regulating bone remodeling [ 61 ]. However, there are few studies on the effects of SMFs on osteocytes.…”
Section: Effects Of Static Magnetic Fields On Bone Remodelingmentioning
confidence: 99%
“…Osteocytes, as endocrine cells, also play an important role in bone-muscle crosstalk [ 1 , 5 , 40 ]. The findings in our recent study indicate that impairment of Cx43-based HCs and GJs in osteocytes respectively decreases fast-twitch muscle mass and muscle contractile force in young mice [ 41 ]. In this study, however, except for the decrease of slow-twitch muscle contractile force in old Δ130–136 mice, we did not observe additional changes in muscle mass or myofiber size.…”
Section: Discussionmentioning
confidence: 99%